Board of directors and small medium enterprise's firm growth with firm culture as moderating factor in Malaysia - Omar, Rosmini; Lim, Kim Yew; Basiruddin, Rohaida (Elsevier Ltd., 2014)
This conceptual paper is based on a study that explores differences of board of directors’ attributes and SMEs firm growth based on firm culture types in Malaysia.The objectives are to explore a model for overall SMEs firm growth based on board of directors’ attributes, to examine the relationship between board entrepreneurial and guanxi in relations with SMEs firm growth.This paper also aims to identify differences of board of directors’ attributes and SMEs firm growth based on firm culture types.One of the most significant theoretical implications is the introduction of a conceptual model on SMEs firm growth, board of directors’ attributes and firm culture based on Malaysia context.From the practitioners’ perspectives, this paper suggests improvement of existing approaches to the governance of SMEs.